2011
DOI: 10.1188/12.onf.100-107
|View full text |Cite
|
Sign up to set email alerts
|

Sociocultural Differences and Colorectal Cancer Screening Among African American Men and Women

Abstract: Purpose/Objectives To examine sociocultural factors that influence an informed decision about colorectal cancer (CRC) screening among African American men and women. Design Descriptive, cross-sectional. Setting A medical center, a National Cancer Institute-designated comprehensive cancer center, and various social organizations and barbershops in a midwestern city of the United States. Sample A purposive sample of African American women (n = 65) and African American men (n = 64) aged 50 years and older. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 32 publications
1
50
0
Order By: Relevance
“…12 Previous research found that social support was predictive of positive beliefs about CRC screening. 12 However, the impact of social support on CRC screening adherence is mixed. 13 …”
Section: Social Supportmentioning
confidence: 99%
See 4 more Smart Citations
“…12 Previous research found that social support was predictive of positive beliefs about CRC screening. 12 However, the impact of social support on CRC screening adherence is mixed. 13 …”
Section: Social Supportmentioning
confidence: 99%
“…12 The relationship between cultural identity and cancer screening behaviors among African Americans is not yet firmly established. The study reported here addresses these gaps in the literature regarding the relationship between cultural identity and the sociocultural factors that impact CRC screening among African Americans.…”
Section: Cultural Identitymentioning
confidence: 99%
See 3 more Smart Citations